2013
DOI: 10.1007/s11481-013-9433-0
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent Effects of Ladostigil on Microglial Activation and Cognition in Aged Rats

Abstract: Ladostigil (1 mg/kg/day) prevents the development of age-related memory deficits by a combination of immunomodulatory and antioxidant effects. A dose causing 30 % ChE inhibition is necessary in order to reverse existing memory deficits at 20 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
8
1
Order By: Relevance
“…The reason for the failure of the control animals to explore the novel object is not clear. While previous research has shown that older rats explore less than younger rats [17] [18], this cannot account for the present Summary of the effects of exposure to HZE particles and protons on the on the dose needed to disrupt object recognition performance on the first (young) and second test (old). The data is presented as log of threshold dose: the dose needed to produce a significant disruption of object recognition memory.…”
Section: Discussioncontrasting
confidence: 68%
“…The reason for the failure of the control animals to explore the novel object is not clear. While previous research has shown that older rats explore less than younger rats [17] [18], this cannot account for the present Summary of the effects of exposure to HZE particles and protons on the on the dose needed to disrupt object recognition performance on the first (young) and second test (old). The data is presented as log of threshold dose: the dose needed to produce a significant disruption of object recognition memory.…”
Section: Discussioncontrasting
confidence: 68%
“…Experiments were performed as previously described, and the interaction by the rats with the objects was videotaped [54]. Since the prepubertal rats were very active, an observation period of 1 min was sufficient to enable the detection of NOR.…”
Section: Methodsmentioning
confidence: 99%
“…Reference memory was assessed in the Morris water maze (MWM) as described previously [54] in 9-10 rats of each sex and prenatal treatment. The rats were given 2 trials a day for 4 days between 10.00 and 14.00 h with an ITI of 30-40 min.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effect of ladostigil on age‐related alterations, previous in vivo studies demonstrated that the drug improved cognitive deficits in aged monkeys (Buccafusco et al ., ) and prevented the development of age‐related memory deficits in aged rats (Weinstock et al ., ; Panarsky et al ., ; Weinstock et al ., ) (Table ). These beneficial effects may be associated with immunomodulatory (microglial activation) and antioxidant effects of ladostigil (Weinreb et al ., ; Weinstock et al ., ). In agreement with this hypothesis, aged rats treated with ladostigil showed an increase in pro‐NGF in various brain regions, presumably resulting from enhanced neuronal activity (Weinstock et al ., ).…”
Section: The Che and Mao Inhibitory Compound Ladostigilmentioning
confidence: 99%